(untitled) (Advancements in Homeopathic Research, 2023)
Irritable Bowel Syndrome (IBS) is a recurrent chronic disorder of gasterointestinal system affecting 10-30% of total worldwide population. Women are more affected than men. Homoeopathy is one of the system of medicine which acts on psychosomatic plane of an individual which can bring IBS to complete cure. Homeopathy is the choice of treatment for all psychosomatic disorders especially for IBS. Management of IBS should concentrate on psychological and behavioral interventions along with proper medication. Reducing mental stress, regular exercises, yoga and meditation will give more beneficial in reducing the severity of IBS.